Challenges of profit-and-loss sharing financing in Malaysian Islamic banking - Aisyah Abdul-Rahman,; Shifa Mohd Nor, (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
There are challenges faced by the profit-and-loss sharing (PLS) financing in Islamic banking institutions in Malaysia. PLS financing is comprised of mudharabah and musharakah contracts. This study evaluated the application and modus operandi of mudharabah and musharakah contracts before dwelling into the challenges. While musharakah contract involves contribution of capital and labor by both the investor and the entrepreneur, mudharabah contract allows the investor to provide the capital and only the entrepreneur operates the business. In terms of return on investment, both partners share the profit or loss based on the pre-agreed ratio for musharakah; but only the capital provider bears the loss for mudharabah as the entrepreneur already forgone his or her effort for the project. In examining the challenges, we had conducted several interview sessions with Malaysian Islamic banks that offer PLS financing. The findings showed that there were four major obstacles to PLS financing such as high risk of investment; difficulty in selecting appropriate partners; demand comes from low credit worthiness customers; and lack of capital security.